PENGARUH PEMBERDAYAAN, ORIENTASI KEWIRAUSAHAAN, DAN KELEMBAGAAN TERHADAP KESEJAHTERAAN PETANI DI SUBAK PULAGAN KECAMATAN TAMPAKSIRING KABUPATEN GIANYAR - Winasari, Ni Made Pertiwi; Budhi, Made Kembar Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The aims of this research is to analyze (1) the influence of farmer empowerment on farmer welfare; (2) The influence of entrepreneurship orientation on farmer welfare; (3) The influence of farmer institution on the farmer welfare; and (4) collectively the farmer empowerment, entrepreneurship orientation, and farmer institutions influence the farmer welfare in Subak Pulagan, Tampaksiring. This research is a quantitative research. The data collection was done through observation, questionnaires, and in-depth-interviews. The number of samples using the Slovin method obtained are 114 farmers. The data collected forward analyzed by descriptive analysis and quantitative analysis through multiple linear regression analysis with SPSS statistic 20 software. The results showed that (1) farmer empowerment had positive influence on farmer welfare in Subak Pulagan, Tampaksiring, Gianyar; (2) The entrepreneurship orientation has positive influence on farmer welfare in Subak Pulagan, Tampaksiring, Gianyar; (3) Farmer institution have positive influence on welfare farmer in Subak Pulagan, Tampaksiring, Gianyar; and (4) Empowerment, entrepreneurship orientation, and institutions together have a positive influence on welfare farmer in Subak Pulagan, Tampaksiring, Gianyar.